Analysis of production resources improvement strategies in make-to-stock environments managed by the simplified drum-buffer-rope system - Govoni, Humberto [UNESP]; de Souza, Fernando Bernardi [UNESP]; Castro, Robson Flávio; de Souza Rodrigues, José [UNESP]; Pires, Silvio Roberto Ignacio (FapUNIFESP (SciELO), 2021)
Theory of Constraints (TOC) states that every system has a single constraint that limits its performance, on which improvement efforts should be concentrated. This paper compared, through computer simulation, several methods of identifying the capacity-constrained resource in the perspective of a process of continuous improvement. Six make-to-stock (MTS) production line configurations managed by the Simplified Drum-Buffer-Rope (S-DBR) system were simulated, in which six improvement methods were applied, three of them based on the TOC literature, and their performance measured and compared in terms of cycle time and order fill rate. The results showed that, in balanced systems, improvements spread over all resources allowed better results, because, in this case, it is necessary to improve everything to benefit the overall performance. In unbalanced environments, on the other hand, the three methods recommended by TOC, which recommend efforts concentrated on the weakest point of the system, achieved superior performance, with emphasis on the strategy based on the level of utilization. In addition to advancing the frontiers of knowledge in continuous improvement and TOC, the research results show that managers should focus their attention on the resource with the highest degree of utilization to get better and faster performance gains.
Análise de estratégias de melhoria de recursos produtivos em ambientes make-to-stock gerenciados pelo sistema tambor-pulmãocorda simplificado
Keywords: Continuous improvement; Make-to-availability; Simplified drum buffer rope; Simulation; Theory of constraints